PELATIHAN CABANG OLAHRAGA BELADIRI KARATE PRAYA TENGAH - Herlina, Herlina; Burhan, Zakir; Ashari, Lalu Hasan; Nulhadi, Agus (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
Karate is a martial art that was developed in China in 1990. Karate is a self-defense technique with bare hands or without weapons." he added "Karate comes from two Kanji letters; kara means empty, while te means hand. Physical education lecturers at the Nusantara Global Institute of Education conduct training for the community to broaden and add to the knowledge of karate martial arts practitioners. By conducting this training, it is hoped that they will provide an understanding for coaches and karate martial arts athletes of the importance of long-term training programs in karate martial arts.